Nursing Maternity: Family Planning - Fenti Hasnani Hasnani (Quality : Jurnal Kesehatan, 2019)
Abstract Non-specific low back pain is the symptom of lower back pain that occurs without an obvious cause, the diagnosis is based on exclusion of specific pathology. Non-specific low back pain can result in pain, muscle spasm and muscle imbalance, it can decrease the stability of the abdominals and lower back, limitation in lumbar mobility , changes posture, and it’s couse make disability in patients with non-specific low back pain. Exercise therapy for non-specific low back pain is high recommend to increased stability and correct posture of the spine. The purpose of this study is to determine the effect of McKenzie Exercise to reduce patient disability in non-specific low back pain. Method: This research applied pre experimental research method with one group Pre and Post Test Design. The research was conducted in Dr Soeradji Tirtonegoro hospital Klaten. There were 16 subjects taken for this research. Disability was measured by oswestry disability index (ODI) before and after treatment. Subject get Mckenzie exercise with the frequens are 2 times a weak in a month Result: Statistical test results obtained, have a decline ODI score at the McKenzie Exercise have done with a value of p = 0.000. This means that Mckenzie excercise can reduce patients disability in non-specific low back pain. Keywords: McKenzie exercises, disability, non-specific low back pain, oswestry disability index.